Frequency, Outcome, and Predictors of Success Within 6 Weeks of an Opioid Rotation Among Outpatients with Cancer Receiving Strong Opioids. (13th December 2012) - Reddy, Akhila; Yennurajalingam, Sriram; Pulivarthi, Kalyan; Palla, Shana L.; Wang, Xuan; Kwon, Jung Hye; Frisbee‐Hume, Susan; Bruera, Eduardo
Abstract : Learning Objectives: Determine the frequency, indications, and outcomes of opioid rotation in cancer outpatients. Describe the predictors of successful opioid rotation. Background: Opioid rotation is used to treat uncontrolled pain and/or opioid‐related adverse effects. Our aim was to determine the frequency, indications, outcomes, and predictors of successful opioid rotation in outpatients with cancer. Methods: Medical records of consecutive outpatients with cancer who received strong opioids and returned for follow‐up visit within ≤6 weeks to our supportive care center from January to December 2008 were reviewed. Data on patient characteristics, symptoms, opioid use, indications for opioid rotation, outcomes, and morphine equivalent daily dose were collected. Successful opioid rotation was defined as a two‐point or 30% reduction in the symptom score or the resolution of opioid‐induced neurotoxicity and continuation of the new opioid at follow‐up. Results: Opioid rotation was performed in 120 of 385 patients (31%). The median patient age was 55 years. There were 6/120 patients with missing data. Of the 114 evaluable patients, 68 (60%) were men, 81 (71%) were white, 27 (24%) had gastrointestinal cancer, and 90 (80%) had advanced‐stage disease. The median Eastern Cooperative Oncology Group score was 1 (interquartile range: 1–2) and the median time between opioid rotation and follow‐up was 14 days (interquartile range: 7–21 days). The most common indications for opioid rotation were uncontrolled pain (95/114; 83%) and opioid‐induced neurotoxicity (13/114; 12%). A total of 35 patients (31%) had partial opioid rotation. The median improvements in pain and symptom distress score were −2 (interquartile range: −4 to 0; p < .001) and −5 (interquartile range: −14 to 7; p = .004), respectively. The morphine equivalent daily dose did not change significantly after opioid rotation ( p = .156). A total of 65% of patients (74/114) had successful opioid rotation. There were no clinically significant independent predictors for successful opioid rotation. Conclusion: Opioid rotation was conducted in 31% of outpatients with cancer, with a 65% success rate. The most frequent reason for opioid rotation was uncontrolled pain. There were no independent predictors for successful opioid rotation. Abstract : This study determined the frequency, indications, outcomes, and predictors of successful opioid rotation in outpatients with cancer who were receiving strong opioids.